Temperature-light-dependent JV and TPV analysis of pure sulfide based Cu2 ZnSnS4 solar cells - Zhengfei Wei (2018 IEEE 7th World Conference on Photovoltaic Energy Conversion (WCPEC) (A Joint Conference of 45th IEEE PVSC, 28th PVSEC & 34th EU PVSEC), 2018)
In this work, we exploit temperature-light-dependent current-density-voltage (T-JV) and transient photovoltage measurements (T-TPV) to investigate charge dynamics, especially at the back contact, in solution-processed Cu 2 ZnSnS 4 solar cells. A Si x N y hole barrier was grown on top of Mo to help to investigate carrier dynamics. By using T-JV techniques, we are able to observe the dominant recombination mechanism occurring at the back contact interface that could lead to significant open-circuit voltage (V oc ) loss. In combination with T-TPV, TPV decay time mapping across temperature in a range of 213-313 K and light intensity range of 0.01-1 suns was used to explore interface related recombination and charge transport for CZTS solar cell devices.